Wild Chimpanzees Infected with 5 Plasmodium Species - Kaiser, Marco; Lowa, Anna; Ulrich, Markus; Ellerbrok, Heinz; Goffe, Adeelia S.; Blasse, Anja; Zommers, Zinta; Couacy-Hymann, Emmanuel; Babweteera, Fred; Zuberbühler, Klaus; Metzger, Sonja; Geidel, Sebastian; et al. (My University, 2010)
Data are missing on the diversity of Plasmodium spp infecting apes that live in their natural habitat with limited possibility of human-mosquito-ape exchange We surveyed Plasmodium spp diversity in wild chimpanzees living in an undisturbed tropical rainforest habitat and found 5 species P malariae P vivax P ovale P reichenowi and P gaboni